TSALATSA QURU’: MEMPERTIMBANGKAN KEMBALI ARGUMEN FIKIH - Cholidi, Cholidi (Universitas Islam Negeri Raden Fatah Palembang, 2016)
Menstrual period (menstruation) and sacred time for a woman is very important. This is because it involves a lot of things and issues in the practice of his religion. Haid past and future is closely related to the implementation of holy prayer, fasting, hajj, the waiting period, mingled with her husband, touching al-Qur`an al-Karim and even read and and others. Another problem that is directly related to the menstrual period is also very important and broad implications is the problem of the waiting period for a wife who divorced by her husband. Ulama of enacting group Shafi sacred significance (not in a state of menstruation) at the quru` pronunciation, while the Hanafi scholars put dirty meanings for the same pronunciation. Two opinions to the contrary are not possible to compromise. Because this issue involves various problems are interrelated, it is deemed very necessary to seek a sensible and accountable to the level of confidence [read: zhon] strong about which of the opinion that it should be guided by the people present. ملخص: فترة الحيض (الدورة الشهرية) ووقت مقدس للمرأة مهم جدا. هذا هو لأنه ينطوي على الكثير من الأمور والقضايا في ممارسة دينه. يرتبط الماضي والمستقبل بشكل وثيق لتنفيذ الصلاة المقدسة، والصوم، الحج، وفترة الانتظار، واختلط مع زوجها، ولمس الكريم وحتى القراءة ووغيرها. مشكلة أخرى ترتبط ارتباطا مباشرا فترة الحيض هو أيضا مهم جدا وآثار واسعة النطاق هي مشكلة فترة الانتظار للحصول على الزوجة التي طلقها زوجها. علماء جماعة سن الشافي أهمية مقدسة (وليس في حالة الحيض) عند النطق، في حين وضع علماء الحنفية المعاني القذرة لنفس النطق. اثنين الرأي على عكس ذلك غير ممكن لتقديم تنازلات. لأن هذه المسألة تتعلق مختلف المشاكل مترابطة، يعتبر من الضروري جدا للتوصل الى معقولة ومسؤولة إلى مستوى قوية حول أي من رأي أنه ينبغي أن يسترشد الحاضرين.